Retrospective observational study comparing hand-assisted, retroperitoneal and trans-abdominal laparoscopic adrenalectomy. (1st March 2022) - Shaw, Alexander; Doran, Helen; Kim, Isaac; Mehra, Sanjay; Fullwood, Catherine; Moinuddin, Zia; Augustine, Titus
Abstract: Aim: Laparoscopic adrenalectomy is considered the optimal approach for most lesions. Various subsets of minimally invasive adrenalectomy are practiced in the UK, including trans-abdominal (TLA), hand-assisted (HLA) and retroperitoneal (RLA) laparoscopic procedures. We aimed to examine the relative operative outcomes between the 3 techniques. Methods: We performed a retrospective observational review of contemporaneously maintained databases from two nearby institutions to establish differences in outcomes between minimally invasive adrenalectomy for any size lesion. Statistical analysis was undertaken using R v3.6.0. Results: Two hundred and ninety-seven patients underwent laparoscopic adrenalectomy and were included in the analysis (45 RLA, 77 HLA and 175 TLA). There were no significant differences between groups for institution location, wound infection, intra-operative bleeding, blood product requirements, visceral injury, open conversion, re-operation, incisional hernia, laterality of lesion, oncological outcomes and medical complications. Boxplots revealed a wider spread and increased mean operating time for TLA, with less difference in operation time between HLA and RLA groups. This was confirmed by an overall significant finding from Kruskal-Wallis rank sum test (p=<0.001) and pairwise comparisons using Wilcoxon rank sum test with a bonferroni correction for multiple testing which demonstrated significant differences between HLA and TLA, and RLA and TLA (p<0.001), but not between RLA and HLA (p=1.000). Conclusion: Minimally invasive adrenalectomy can safely be performed by any of 3 techniques. TLA showed a longer mean operating time. The analysis of outcomes revealed otherwise no significant differences in operative or medical outcomes.